The Effect of Narcotics, Psychotropic, and Addictive Substance Counseling toward SMK Students Knowledge about Drug Abuse - Hasanah, Dwiatri Harjanti Uswatun; Murtiati, Tri; Rahayu, Sri (Universitas Negeri Jakarta, 2014)
Understanding about narcotics, psychotropics, and addictive substances is beneficial to prevent drugs abuse among students. One of the ways to provide knowledge about this topic may be done by counseling. This research was aimed to know the effect of narcotics, psychotropics, and addictive substances counseling toward students’ knowledge about drug abuse. The study was conducted in SMK Negeri 34 Jakarta during May 2012 using an experimental method. Simulation method was performed in experimental class whether speech method was applied in control group. This research design was pretest-posttest control group using multiple choice knowledge test instrument. Samples were selected by simple random sampling. Normality testing of the Kolmogorov Smirnov test and homogeneity testing of t-test showed a normal distribution and homogenous data. Meanwhile, hypothesis testing done by t-test at α = 0.05 result was t table < t count < ttable at -3.23 < -0.67 < 2.03, meaning that there was no effect of narcotics, psychotropics, and addictive substances counseling toward students knowledge about drugs abuse.